2017
DOI: 10.1177/1464884917722453
|View full text |Cite
|
Sign up to set email alerts
|

Valuing subjectivity in journalism: Bias, emotions, and self-interest as tools in arts reporting

Abstract: This article examines the meanings and norms surrounding subjectivity across traditional and new forms of cultural journalism. While the ideal of objectivity is key to American journalism and its development as a profession, recent scholarship and new media developments have challenged the dominance of objectivity as a professional norm. This article begins with the understanding that subjectivity is an intractable part of knowing (and reporting on) the world around us to build our understanding of different m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 60 publications
0
17
0
2
Order By: Relevance
“…In research on the culture of arts journalists, Harries and Wahl-Jorgensen (2007) indicated why journalists reporting on a cultural artifact could consider themselves journalists, but yet 'exceptional within the culture of journalism' (p. 635). Indeed, arts criticism has sat uncomfortably within journalism: (1) arts journalists are journalists but need specialist knowledge in order to communicate to the public the complicated nature of artifacts, (2) arts coverage does not fit easily into 'hard news' categories, yet arts journalists would describe their work as more important than traditional news, and (3) arts journalists subscribe to notions of objectivity, although objectivity has 'less relevance' in this form of journalism (Harries and Wahl-Jorgensen, 2007: 635), since subjectivity is largely inseparable from arts reporting (Chong, 2019). But whereas arts journalists ultimately claim that art improves society (Harries and Wahl-Jorgensen, 2007), gaming journalists do not make such claims about games (Foxman and Nieborg, 2016).…”
Section: Covering Gamingmentioning
confidence: 99%
“…In research on the culture of arts journalists, Harries and Wahl-Jorgensen (2007) indicated why journalists reporting on a cultural artifact could consider themselves journalists, but yet 'exceptional within the culture of journalism' (p. 635). Indeed, arts criticism has sat uncomfortably within journalism: (1) arts journalists are journalists but need specialist knowledge in order to communicate to the public the complicated nature of artifacts, (2) arts coverage does not fit easily into 'hard news' categories, yet arts journalists would describe their work as more important than traditional news, and (3) arts journalists subscribe to notions of objectivity, although objectivity has 'less relevance' in this form of journalism (Harries and Wahl-Jorgensen, 2007: 635), since subjectivity is largely inseparable from arts reporting (Chong, 2019). But whereas arts journalists ultimately claim that art improves society (Harries and Wahl-Jorgensen, 2007), gaming journalists do not make such claims about games (Foxman and Nieborg, 2016).…”
Section: Covering Gamingmentioning
confidence: 99%
“…First of all, journalism scholars (as well as journalists) have used and continue to use different terminologies for this type of journalism. Some use the inclusive term "lifestyle journalism" (e.g., Fürsich, 2012;Hanusch, 2012Hanusch, , 2017, others the more exclusive term "arts journalism" (e.g., Chong, 2017;Harries & Wahl-Jorgensen, 2007;Sarrimo, 2017), while still others focus on particular cultural sub-beats, such as music journalism, food journalism, and fashion journalism (e.g., Bradford, 2014;Turner & Organge, 2013). This lack of terminological consensus has made cultural journalism a less demarcated research area.…”
Section: Diverse Terminologies About Cultural Journalismmentioning
confidence: 99%
“…As Blank states (2007, p. 4) in his work on critics, reviews, and ratings, reviewers must convince, i.e., persuade, the cultural public or cultural consumers of their arguments, which influences the rethorical strategies applied. Chong (2017), among others, outlines how arts and cultural journalists are driven by different types of subjectivism, especially in reviews: bias, e.g., which cultural works are chosen for review, aka cultural gatekeeping; emotionality in terms of critical tone; and self-interest in terms of balancing self-publicising and giving due consideration for the work under review. In addition, cultural journalism and cultural criticism have a tradition of being performed by not only professionally trained journalists but also public intellectuals, critical thinkers, academics, and cultural columnists (e.g., Kristensen & From, 2015b;Riegert et al, 2015;Sarrimo, 2017) adhering to truth claims grounded in subjectivity, analysis, and expertise.…”
Section: Epistemologiesmentioning
confidence: 99%
“…What journalistic roles are there, then? This question is not easily answered, as journalistic roles vary not only in different contexts, but also because different 31 For example, Chong (2017) found that cultural journalists often value personal style (or voice) over neutrality. 32 In this idealistic setting individual journalists have the autonomy to actually put into practice what they believe is important -which is seldom the case (Mellado et al, 2017a).…”
Section: Journalistic Rolesmentioning
confidence: 99%